Phenotypic and genetic variation in lumpfish (Cyclopterus lumpus): applications towards sustainable aquaculture of cleaner fish - BENJAMIN WHITTAKER (2020)
Ectoparasitic lice threaten sustainable Atlantic salmon (Salmo salar) aquaculture, as high farm stocking densities facilitate louse infestation thereby increasing mortality rates. Lumpfish (Cyclopterus lumpus) have recently been demonstrated to remove lice and are increasingly deployed onto farms as cleaner fish. Commercial stocks of lumpfish are now produced in hatcheries to meet growing demand from farms across the Atlantic, however, concern grows regarding the long-term viability of this practise due to insufficient knowledge on lumpfish biology. Challenges include understanding how patterns of genetic and phenotypic variation influence performance, whether desirable traits can inform captive breeding, potential impacts on wild populations and whether intraspecific variation in cleaning behaviour can be optimized. Therefore, this thesis examined genetic and phenotypic variation in lumpfish across multiple biological scales, ranging from populations down to family stocks and individuals, investigating factors influencing aquaculture performance. Chapter 1 found genetic structure in populations across the Atlantic, with limited gene flow separating regions of lumpfish aquaculture. Chapter 2 identified phenotypic differences in the body morphology of stocks, including variation in scutes and body depth of northern and southern phenotypes. Sexual dimorphism was identified in the mouth, flag, hump and caudal peduncle. Chapter 3 showed further phenotypic differences in fitness-related traits, with faster growth, more active swimming and lower survival associated with northern stocks. Chapter 4 developed protocols to quantify lumpfish personality and found that bolder individuals interacted more with salmon, whereas, a syndrome for social-aggression was linked to antagonistic behaviour. Patterns of genetic and phenotypic variation imply population differentiation is reflected in stocks commonly used in aquaculture. Common-garden trials suggested translocated lumpfish show reduced fitness, therefore establishing regionally-specific stocks may benefit performance and minimise detriment to wild populations via introgression through farm escapes. Personality constituted a major source of variation in cleaning behaviour, selecting bold lumpfish could optimise efficiency.